2018
DOI: 10.1016/j.neuron.2018.07.047
|View full text |Cite
|
Sign up to set email alerts
|

Generative Predictive Codes by Multiplexed Hippocampal Neuronal Tuplets

Abstract: Rapid internal representations are continuously formed based on single experiential episodes in space and time, but the neuronal ensemble mechanisms enabling rapid encoding without constraining the capacity for multiple distinct representations are unknown. We developed a probabilistic statistical model of hippocampal spontaneous sequential activity and revealed existence of an internal model of generative predictive codes for the regularities of multiple future novel spatial sequences. During navigation, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 66 publications
3
48
0
Order By: Relevance
“…That is, upon presentation of a predictive cue or context, the hippocampus may retrieve the associated outcome through pattern completion (14,21), regardless of the exact nature of the stimuli. This is in line with evidence that the hippocampus is involved in many different types of predictions, pertaining to, for example, faces and scenes (22), auditory sequences (23), odors (24), and spatial locations (19,25).…”
Section: Introductionsupporting
confidence: 89%
“…That is, upon presentation of a predictive cue or context, the hippocampus may retrieve the associated outcome through pattern completion (14,21), regardless of the exact nature of the stimuli. This is in line with evidence that the hippocampus is involved in many different types of predictions, pertaining to, for example, faces and scenes (22), auditory sequences (23), odors (24), and spatial locations (19,25).…”
Section: Introductionsupporting
confidence: 89%
“…First, the place fields tend to get larger further into the linear track (Gothard et al 1996;Haas et al 2019), indicating that fields late in a sequence accumulate more sensory information. Second, Liu et al (2018a) found evidence for prewired sequence motifs being shorter than the observed sequences. The length of the sequences in the model of Appendix A varies with mean synaptic weights and as a function of all other parameters defining neuronal excitability, hence, arguing that transitions from short to long sequences can result from general excitability increases.…”
Section: Discussionmentioning
confidence: 88%
“…A potential criticism to the model arises from physiological reports that offline sequences are plastic and change from preplay to replay mostly by adding new neurons (Grosmark and Buzsaki 2016;Liu et al 2018a;Chenani et al 2019), whereas in the present model the sequences remain fixed. There are two ways to explain sequence plasticity in the realm of this model.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Place cell activity appears to contain an abundance of certain short sequences that represent contiguous locations in novel environments and participate frequently in replays [112]. This finding is related to the disputed [113] observation of hippocampal preplay [114][115][116].…”
Section: Possible Implicationsmentioning
confidence: 99%